Unravelling the formation of Hells Bells: underwater speleothems from the Yucatán Peninsula [data] - Ritter, Simon M. (Universität, 2019)
Hells Bells are unique bell-shaped underwater speleothems recently discovered in deep meromictic sinkholes (cenotes) on the Yucatán Peninsula, Mexi...
Gesehen am 16.12.2019
Keywords: Forschungsdaten; Datenbank; Hells Bells; Speläothem; Halbinsel Yucatán